Synthesis and Characterization of Hydroxyapatite Using Precursor Extracted From Seashell Waste - Rosley, Rozainita; Posharani Saravanan,; Sharrmitah Saravanakumar, (Multidisciplinary Applied Research and Innovation, 2024)
Seashells contain CaCo3 and can cause environmental problem due to the microbes and bacteria activity in the shells. However, the waste can be mitigated and used to use the high calcium content. It can converted into hydroxyapatite (Hap). Hap is bioactive and biocompatible and has been used for several biomedical applications. Synthesizing Hap from natural sources can be contribute significantly towards natural resource management, health care, waste utilization amongst others. The focus of research is to make the whole process eco-friendly, economical and minimal waste generating. The synthesis of Hap was carried out through a calcination method with different weight of seashell powder where the precursor material was reacted with a calcium and phosphate-containing solution under controlled conditions. The synthesized hydroxyapatite samples were characterized using various analytical techniques. X-ray diffraction (XRD) analysis was performed to determine the phase purity and crystal structure of the synthesized hydroxyapatite. Scanning electron microscopy (SEM) was employed to study the morphology and particle size of the Hap crystals. Additionally, Fourier-transform infrared spectroscopy (FTIR) was used to identify the functional group present in the Hap structure. From the various analytical techniques, 30g of seashell powder showed the highest peak in XRD analysis and FTIR analysis displayed the broad and strong absorption of Hap. The Hap derived from seashell waste was synthesized and validated from the results. The synthesized Hap possesses desirable characteristics for biomedical applications, making it a promising material for future research and development in the field of regenerative medicine and biomaterials.